Plasmid Borne Resistance in Klebsiella Isolates from Kenyatta National Hospital, Nairobi, Kenya. (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Eighty six Klebsiella isolates from Kenyatta National Hospital and the Centre for Microbiology, Kenya Medical Research Institute, Nairobi were screened for resistance to commonly prescribed antimicrobial agents and for their plasmid content. Plasmids were transferred into Esherichia coli K-12 and resulting transconjugants screened for resistance to the antimicrobial agents used on Klebsiella donors and for their plasmid content. Plasmids from the Klebsiella isolates were also transformed into Eschericia coli and transformants analyzed for resistance and plasmid content. Endonuclease restriction mapping was done to characterize the plasmids from Klebsiella isolates and their Eschericia coli transformants. Resistance was found to be plasmid borne and transmissible
Keywords: Plasmid; resistance; conjugation; transformation